2021
DOI: 10.1038/s41598-021-90878-0
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced B4C electrodes for high energy density supercapacitor devices

Abstract: Boron carbide powders were synthesized by mechanically activated annealing process using anhydrous boron oxide (B2O3) and varying carbon (C) sources such as graphite and activated carbon: The precursors were mechanically activated for different times in a high energy ball mill and reacted in an induction furnace. According to the Raman analyses of the carbon sources, the I(D)/I(G) ratio increased from ~ 0.25 to ~ 0.99, as the carbon material changed from graphite to active carbon, indicating the highly defecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These results are in great agreement with the CV and PEIS results, further confirming that the morphology has a significant effect on the electrochemical performances of boron carbide electrodes. Different morphologies of boron carbide may contain different defect structures with different concentrations, which play a direct role in enhancing the electrochemical performance of the device by providing additional pathways for ion transport [ 34 , 56 ]. Defects can be controlled by alternating the morphology, which can be tailored by employing different synthesis routes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in great agreement with the CV and PEIS results, further confirming that the morphology has a significant effect on the electrochemical performances of boron carbide electrodes. Different morphologies of boron carbide may contain different defect structures with different concentrations, which play a direct role in enhancing the electrochemical performance of the device by providing additional pathways for ion transport [ 34 , 56 ]. Defects can be controlled by alternating the morphology, which can be tailored by employing different synthesis routes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Chang et al demonstrated that core–shell structure B 4 C@C can also be employed as an electrode material for all-solid-state micro-supercapacitors [ 33 ]. In addition, the roles of intrinsic defects in the electrochemical performance of B 4 C electrodes have also been studied [ 34 ]. Moreover, boron carbide has excellent chemical stability and low-volume expansion [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transition metal silicides possess excellent interface properties with silicon and obtain low internal resistance because they are binder-free electrode materials (Ramly et al, 2018). It is worth noting that in addition to the above advantages, transition metal silicides also show intentional electrochemical properties, such as high theoretical energy FIGURE 5 | A brief timeline of the developments of promising of MSCs (In et al, 2008;Balcı et al, 2021;Yang et al, 2021a).…”
Section: Transition Metal Silicidementioning
confidence: 99%
“… A brief timeline of the developments of promising of MSCs ( In et al, 2008 ; Balcı et al, 2021 ; Yang et al, 2021a ). …”
Section: Materials For Micro-supercapacitorsmentioning
confidence: 99%
“…The low density and specific gravity make it ideal for use as lightweight armour and for space applications where protection from space debris impacts and resistance to radiation are both prerequisites in addition to maximizing the load–fuel ratio. Boron carbide is also used as a control material in thermal and fast reactors [ 3 ] and supercapacitor material [ 4 ]. Boron carbide is, however, shown to exhibit enigmatic behaviour under static and dynamic pressures that suggest the possibility of an elastic anomaly and loss of shear strength above 20 GPa.…”
Section: Introductionmentioning
confidence: 99%